The Academic Endeavour: 1956–2016–???? - Keith, Kenneth J (Victoria University of Wellington Law Review, 2017)
Massive changes have occurred in the last 60 years in law teaching, legal practice and the law, and in the contexts, national and international, in which the law and legal processes operate. Further large changes are likely in the short as well as the long-term. What may be learned from the existing experience for law teaching and research and for the role of the academic as critic and conscience of society? This address was given at the Australasian Law Teachers Association (ALTA) 2016 Conference held in Wellington on 8 July 2016.